Medjugorje: Harmony and Conflict of Symbols, Narratives and Rituals - Belaj, Marijana (Array, 2011)
The topic of this paper is Medjugorje, a pilgrimage centre, observed through mutually constituting relations of people and space. The author will examine the construction of toposes of Medjugorje through symbols, narratives and (ritual) practices, and how those toposes influence the renegotiating of identity of those using them. Those constituting processes turn Međugorje into a space of simultaneous harmony and conflict, the freedom of its creation being one of its prominent features